Identification of New Phosphate Solubilizing Bacteria and Application Guidelines - Klumsuk, Chayanid; Athinuwat, Dusit (Thai Journal of Science and Technology, 2022)
The purpose of this study was screening the phosphate solubilizing bacteria (PSB) to enhance plant growth in agroecosystem. Forty-one rhizosphere bacterial strains were isolated from bamboo rhizosphere soil at Pathum Thani province with completely randomized design (CRD). Ten out of 41 strains showed phosphate solubilization capacity on Pikovskaya’s agar. The PSB28 and PSB15 were the most efficient bacterial isolates for phosphate solubilization as showed the largest clear zone diameter with 2.13±0.07 and 1±0.26 cm, respectively (p<0.05). Gram stain and hypersensitive response test revealed that PSB28 and PSB15 were Gram negative and Gram positive, respectively. Therefore, PSB15 was selected to test for ability to solubilized phosphate with different phosphate resource including calcium phosphate (Ca3(PO4)2), rock phosphate, and ammonium dihydrogen phosphate ((NH4)H2PO4). The result showed that calcium phosphate (Ca3(PO4)2) was most capable source of phosphate dissolved by PSB15 as showed available phosphorus in total amount of 69.67±1.8, 60.80±8.66, and 59.96±8.31 mg/kg at 7, 14, and 21 days, respectively. For identification of PSB15, the 16S rRNA of gene sequencing was applied with two universal primers, 27F (5’-AGA GTT TGA TCM TGG CTC AG-3’) and 1492R (5’-CGG TTA CCT TGT TAC GAC TT-3’). The results of analysis showed the yielded of sequences was similarity score of ≥ 98% with the sequences of Bacillus paramycoides in GenBank. When PSB15 was applied with rice seedling, it showed high efficiency on plant growth promotion. It can be mixed used or substituted chemical fertilizer to enhance available phosphorus in soil and increase plant growth. These results revealed that application of phosphate solubilizing bacteria, B. paramycoides PSB15 with phosphate resource in agroecosystem can be an alternative method to reduce the use of synthetic fertilizer.